2015
DOI: 10.1097/jto.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Irreversible ErbB Family Blocker Afatinib in Epidermal Growth Factor Receptor (EGFR) Tyrosine Kinase Inhibitor (TKI)–Pretreated Non–Small-Cell Lung Cancer Patients with Brain Metastases or Leptomeningeal Disease

Abstract: Introduction:Afatinib is an effective first-line treatment in patients with epidermal growth factor receptor (EGFR)-mutated non–small-cell lung cancer (NSCLC) and has shown activity in patients progressing on EGFR-tyrosine kinase inhibitors (TKIs). First-line afatinib is also effective in patients with central nervous system (CNS) metastasis. Here we report on outcomes of pretreated NSCLC patients with CNS metastasis who received afatinib within a compassionate use program.Methods:Patients with NSCLC progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
182
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(193 citation statements)
references
References 47 publications
8
182
2
1
Order By: Relevance
“…Recently, the T790M mutation was reported to occur more frequently in extracranial lesions than CNS lesions (1, 13, 14), indicating that the presence of the T790M mutation in the extracranial lesion does not always correspond to the positivity of the T790M mutation in the CNS lesion. In addition, the superior effect of afatinib over first-generation EGFR-TKIs on CNS lesions has also been demonstrated in the following two reports: Hata et al reported a case of T790M-negative NSCLC with BM, which developed during erlotinib treatment but responded to afatinib immediately after erlotinib therapy (15); and Hoffknecht et al reported that CNS metastases were controlled by afatinib in 66% of patients heavily treated with first-generation EGFR-TKIs (16). In the report by Hoffknecht et al, a case of T790M-positive adenocarcinoma with LMC was successfully treated with afatinib, which reached an effective concentration in the cerebral spinal fluid (CSF), although the penetration rate remained less than 1% (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the T790M mutation was reported to occur more frequently in extracranial lesions than CNS lesions (1, 13, 14), indicating that the presence of the T790M mutation in the extracranial lesion does not always correspond to the positivity of the T790M mutation in the CNS lesion. In addition, the superior effect of afatinib over first-generation EGFR-TKIs on CNS lesions has also been demonstrated in the following two reports: Hata et al reported a case of T790M-negative NSCLC with BM, which developed during erlotinib treatment but responded to afatinib immediately after erlotinib therapy (15); and Hoffknecht et al reported that CNS metastases were controlled by afatinib in 66% of patients heavily treated with first-generation EGFR-TKIs (16). In the report by Hoffknecht et al, a case of T790M-positive adenocarcinoma with LMC was successfully treated with afatinib, which reached an effective concentration in the cerebral spinal fluid (CSF), although the penetration rate remained less than 1% (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the superior effect of afatinib over first-generation EGFR-TKIs on CNS lesions has also been demonstrated in the following two reports: Hata et al reported a case of T790M-negative NSCLC with BM, which developed during erlotinib treatment but responded to afatinib immediately after erlotinib therapy (15); and Hoffknecht et al reported that CNS metastases were controlled by afatinib in 66% of patients heavily treated with first-generation EGFR-TKIs (16). In the report by Hoffknecht et al, a case of T790M-positive adenocarcinoma with LMC was successfully treated with afatinib, which reached an effective concentration in the cerebral spinal fluid (CSF), although the penetration rate remained less than 1% (16). Taking those reports into consideration together with the present case, afatinib treatment should be considered for CNS metastases, regardless of the presence of the T790M mutation in the extracranial lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five percent of evaluable patients developed a CNS response with median duration response of 120 days. One patient who developed a response on 40 mg of oral afatinib, achieved a CSF afatinib concentration of about 1 nM [86].…”
Section: Cns Penetrationmentioning
confidence: 99%
“…indicated superior clinical effect of afatinib on the central nervous system metastasis [16] . Afatinib has toxicities that are similar to gefitinib or erlotinib, such as diarrhea, skin rash, stomatitis and interstitial pneumonia.…”
mentioning
confidence: 99%